Study of the effectiveness of a home-based pulmonary therapy program in Ecuadorian older adults with prolonged exposure to biomass smoke based on Plithogenic Similarity Measure - Lisbeth Josefina Reales Chacón; Javier Patricio Heredia Jiménez; Lizbeth Geovanna Silva Guayasamín; Christian Andrés Silva Sarabia; María José López Pino; Javier Caiza Lema; Josselyn Gabriela Bonilla-Ayala (Neutrosophic Sets and Systems)
Biomass is a form of energy used primarily by people living in rural areas of developing countries. This type of energy is based on the combustion of elements such as wood. Exposure to biomass is linked to diseases such as Chronic Obstructive Pulmonary Disease (COPD), which is a major cause of global mortality. In this paper, we study a group of patients of 65 and over years of age exposed to biomass smoke for long periods in the Ecuadorian province of Cotopaxi. Specifically, we study the effectiveness of a home-based pulmonary rehabilitation program. Since there are different variables to measure, we use plithogenic sets. These also allow us to deal with the uncertainty and indeterminacy inherent in measuring subjective variables. We design a procedure that allows us to classify cases where improvement or lack of progress is evaluated after treatment.